MARKET STRATEGY ANALYSIS: A CONCEPTUAL STUDY OF RED OCEAN VERSUS BLUE OCEAN - Putri Qonitah Rahim; Sitti Syamsiah; Murtiadi Awaluddin; Sudirman (Al Tijarah, 2024)
In the dynamic world of business, competition is a critical aspect that demands strategic attention. The ability to design effective strategies to navigate market challenges is essential for business success. Two prominent approaches in this domain are the Blue Ocean Strategy (BOS) and the Red Ocean Strategy (ROS). BOS focuses on creating new, innovative market spaces where competition becomes irrelevant by delivering unique value. Conversely, ROS emphasizes direct competition in existing markets, aiming to outperform rivals through competitive advantages. This study aims to analyze the concepts and applications of BOS and ROS, exploring the fundamental differences between these approaches and their implications for managing business competition. Through a conceptual approach, this review highlights how these strategies can be integrated to strengthen market positioning, enhance competitiveness, and create sustainable value. Furthermore, the study underscores the potential of BOS and ROS to assist businesses in navigating the ever-evolving dynamics of the global market. This comprehensive analysis is intended to provide strategic insights for business practitioners in selecting and implementing approaches that best align with their objectives.